2020
DOI: 10.1007/s00268-020-05486-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Laparoscopic Gastrectomy More Advantageous for Elderly Patients Than for Young Patients with Resectable Advanced Gastric Cancer?

Abstract: Background Laparoscopic gastrectomy (LG) is now practiced widely, but it is unclear whether LG is the appropriate approach for elderly patients with resectable advanced gastric cancer. The aim of this study was to examine whether LG is more or less advantageous for elderly patients than for young patients. Methods We collected data on 571 consecutive patients who underwent gastrectomy for pT2-4 gastric cancer between January 2001 and December 2015. After adjustment with one-to-one propensity score matching, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Shimada et al showed that although 5-year OS was signi cant lower in the elderly group than in the non-elderly group, 5-year DSS was similar in the two groups, as with our results [30]. Ushimaru et al reported that although DSS was similar between the laparoscopic and open groups among young and elderly patients, the laparoscopic group was associated with more favorable OS than the open group only among the elderly patients because of the lower number of deaths from respiratory diseases [31]. Some reports indicated that the incidence of postoperative complications was an important factor that in uenced long-term outcomes [24,[32][33][34]].…”
Section: Discussionsupporting
confidence: 88%
“…Shimada et al showed that although 5-year OS was signi cant lower in the elderly group than in the non-elderly group, 5-year DSS was similar in the two groups, as with our results [30]. Ushimaru et al reported that although DSS was similar between the laparoscopic and open groups among young and elderly patients, the laparoscopic group was associated with more favorable OS than the open group only among the elderly patients because of the lower number of deaths from respiratory diseases [31]. Some reports indicated that the incidence of postoperative complications was an important factor that in uenced long-term outcomes [24,[32][33][34]].…”
Section: Discussionsupporting
confidence: 88%
“…A previous study by our group indicated the potential benefits of laparoscopic gastrectomy for elderly patients with resectable GC [20]. Ushimaru et al [21] reported that laparoscopic gastrectomy might improve the OS by reducing mortality from respiratory diseases. Still, the benefit of adjuvant chemotherapy after laparoscopic D2 gastrectomy in elderly patients is unknown.…”
Section: Introductionmentioning
confidence: 89%
“…Shimada et al showed that although 5-year OS was significant lower in the elderly group than in the non-elderly group, 5-year DSS was similar in the two groups, as with our results [ 30 ]. Ushimaru et al reported that although DSS was similar between the laparoscopic and open groups among young and elderly patients, the laparoscopic group was associated with more favorable OS than the open group only among the elderly patients because of the lower number of deaths from respiratory diseases [ 31 ]. Some reports indicated that the incidence of postoperative complications was an important factor that influenced long-term outcomes [ 24 , 32 34 ].…”
Section: Discussionmentioning
confidence: 99%